A fundamental study of spinel Co3O4 electro-catalyst durinf electrochemical oxygen evolution reaction - Wang, Hsin-Yi (2016)
The energy crisis and related environmental issue is an important issue at a global level. Water electrolysis has been proposed as a promising technology for the production of H2 that can be directly used as the clean fuel. However, the efficiency of the electrolyser is greatly limited on the anode side, where the oxygen evolution reaction (OER) is a thermodynamic up-hill reaction and which usually requires a high overpotential to drive the reaction. Thus, efficient and earth-abundant electrocatalyst for high-performance OER is essential for the development of sustainable energy conversion technology. Spinel cobalt oxide (Co3O4) is an earth-abundant element which has been extensively studied as effective OER catalyst due to its competitive activity compared to the noble catalyst. To further improve the catalytic activity, substituting Co3O4 with Ni has been proposed as a promising approach to enhance the electrochemical activity toward OER. We revealed that by tuning the amount of the coordinating agent of NH3+ and/or F- ions, the Ni dopant was capable of enlarging the surface roughness factor, improving the electrical conductivity of the catalyst, and reducing the activation energy barrier in terms of a relatively earlier onset with a high current density. Meanwhile, we also found the Ni dopants occupied the tetrahedral site of the spinel structure, which could be a critical information because so far, although it has been known the spinel Co3O4 was comprised by one Co2+ in the tetrahedral site (Co2+Td) and two Co3+ in the octahedral site (Co3+Oh), the roles of two geometrical cobalt ions toward the OER have remained elusive. To individually understand geometrical-site-dependent OER activity of Co3O4 catalyst, we separately examined the properties of Co3+Oh and Co2+Td by substituting Co2+Td and Co3+Oh with inactive Zn2+ and Al3+, respectively. Following a thorough in-operando analysis by electrochemical impedance spectroscopy and X-ray absorption spectroscopy, it was revealed that Co2+Td site is responsible for the formation of cobalt oxyhydroxide (CoOOH), which acted as the active site for water oxidation. Apart from the geometrical-site-dependent activity of spinel Co3O4 has been successfully disclosed, we were also surprised that the anodic peak prior to the rise of OER current could be vanished if Zn2+ was substituted into the tetrahedral site of Co3O4. Thus, the underlying properties of oxidation peak attracted our attentions. Through a combination of well-designed independent in-situ measurements including X-ray absorption and grazing-angle X-ray diffraction under operando conditions, and following a potential-resolved in-situ Raman analysis with their particularly re-designed in-situ cell, we successfully revealed that the anodic peak current could be associated with the formation process of peroxide moieties (e.g., Co-OO-Co or Co-OOH) on the surface of Co3O4, and more importantly, Co2+Td ions in Co3O4 should be the vital species to bridge the µ-OO bond as the key elementary step for the OER. In this thesis, we step-by-step revealed the full OER mechanism on spinel Co3O4 electrocatalyst carefully and rationally via various operando measurements. We wanted to highlight that by doing such detailed study, a rational design for a superior catalyst with highly effective activity is possible.